PEMBERDAYAAN UMKM JAHE INSTAN MELALUI INOVASI PEMASARAN BERBASIS MEDIA SOSIAL - Nurani; Hariatih; Nur Syamsinar Munir; Yakub; Nurul Fitriah Rahman; Sri Endarti Halim (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This community service activity was conducted in Barugae Village and aimed to empower instant ginger UMKM by improving digital literacy and implementing social media-based marketing innovations. UMKM play a vital role in the Indonesian economy, but the low utilization of social media as a marketing tool results in limited exposure to local products. This activity employed a participatory approach, including needs identification, development of training modules, digital literacy training, implementation support, and monitoring and evaluation. The results demonstrated improved participant skills in creating social media business accounts, designing creative promotional content, and utilizing interactive features to expand market reach. Furthermore, UMKM motivation to innovate in digital marketing strategies increased, resulting in an increase in social media followers and increased demand for instant ginger products. This activity emphasized the crucial role of innovation and social media in facing competition and serving as a sustainable model for strengthening the competitiveness of superior village products.